Utilization of steel industry slag for removal of copper and manganese - Beh, Chin Lai (2011)
Steel making slag from Electric Arc Furnace (EAF) is a major abundant by-product in Malaysia steel industry. It has potential to be used as low cost adsorbent for heavy metal removal from waste water. The aim of this study is to develop an innovative approach by using this EAF slag (EAFS) for heavy metals absorption particular manganese and copper in steel industry waste water. The removal characteristics and behavior of manganese and copper were investigated in term of adsorption kinetics and isotherm as well as the adsorption capacity in batch and fixed bed column system. In addition, the effects of the contact time, pH, temperature, particle size were determined in batch process and the effects of the bed depth and flow rate were examined in the fixed bed column system. Furthermore, the real waste water from steel making process was also carried out as case study in order to determine the practical aspect of the EAFS performance. It is found that the EAFS adsorption kinetics can be described well by the Pseudo-2nd order kinetic model with fairly high correlation coefficients. The adsorption process obeyed the Langmuir isotherm model and the maximum uptake of the manganese and copper from the solution are 2.30 mg/g and 2.69 mg/g respectively. In binary adsorption, it can be seen that the amount of adsorption for both the metals are less than in single system. Thus, the difference of adsorption capacity showed that there was a competitive adsorption of the metal ion on the surface of EAFS. The optimum pH and temperature was observed to be at pH 8 and 28oC respectively for the maximum removal of both the manganese and copper. The equilibrium time was determined at 5 hours and 3 hours for manganese and copper respectively and it is noticed that both the metals adsorption capacity increase as the particle mean size of the EAFS decrease from 4mm to 1mm. The bed depth service time (BDST) model fitted well with the experimental data where the service time increased accordingly when the bed depth is increased. Thomas model also described well the adsorption behavior of the effect of flow rate on adsorption capacity and breakthrough curves. It is observed that the pH of the solution will be slightly increased from 7 to 8 due to the formation of calcium hydroxide (CaOH) from calcium oxide (CaO) present in the EAFS. From the study, it was concluded that the EAFS can be an efficient low cost adsorbent to remove heavy metals particularly manganese and copper from steel industry waste water.